Smart techniques and tools to detect Steganography - a viable practice to Security Office Department - Moura, João Carlos Zêzere da Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management